Epidemiological Status of Brucellosis in Abadeh County, Fars Province, Iran in 2011-2017 - Ahmad karimi; Behnam karimi (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: Brucellosis is one of the most common zoonotic diseases in many parts of the world, which has made problems for the public health and the livestock economics. The aim of this study was to investigate the epidemiological status of brucellosis disease in Abadeh county, Fars province, Iran.  Methods: In this cross-sectional study, the demographic and epidemiologic data of 985 patients with brucellosis who referred to the health centers and clinics of Abadeh county from 2011 to 2017 were evaluated. In order to analyze the data, the frequency distribution, Chi-Square and independent t-test statistical models were used through the SPSS version 25. A significant level of 0.05 was considered. Results: The incidence of the disease in 2011-2017 was 128.78 per 100,000 population. Most cases of the disease were reported in the spring and summer. The highest number of people with the brucellosis consisted of housewives (28.7%), ranchers (25.4%), and students and pupil (17.8%). In addition, 56 percent of the patients were the rural inhabitants. We found that 62.6 percent of the patients had a history of contact with the livestock and non-pasteurized cheese was the source of infection transmission to humans in 50.2 percent of the cases. The mean age of the patients was 34.3 ± (19.35) years and the age group of 25-34 years had the highest number of patients (20.9). which is the prevalence of the disease in men was one and a half times higher than this rate in women. Conclusion: Regarding the high prevalence of brucellosis disease in Abadeh city, training about the ways of disease transmission should be provided to various population groups, especially the individuals who are at risk.